2021
DOI: 10.1016/j.asmr.2021.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Glenoid Bone Augmentation Using Iliac Crest Autograft Is Safe and Effective for Anterior Shoulder Instability With Bone Loss

Abstract: Purpose: To establish a safety profile for an arthroscopic anatomic glenoid reconstruction using autologous iliac crest bone graft to treat shoulder instability with significant bone loss and to evaluate short-term clinical and radiological outcomes. Methods: A retrospective analysis of prospectively collected data was conducted for the patients who were treated for shoulder instability with bone loss using arthroscopic autologous iliac crest bone graft between November 2014 and June 2018. The safety profile w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…This surgical procedure can be used as a revision after the failure of the Latarje and Bristow procedure or as a repair when the bone defect is huge. As for the choice of free bone graft, autogenous iliac crest is more common, but the complication rate is higher [ 23 , 24 ]. Meanwhile, studies using allograft distal tibia, autogenous distal clavicle, and autologous scapular spine as grafts have also been reported [ [25] , [26] , [27] ].…”
Section: Discussionmentioning
confidence: 99%
“…This surgical procedure can be used as a revision after the failure of the Latarje and Bristow procedure or as a repair when the bone defect is huge. As for the choice of free bone graft, autogenous iliac crest is more common, but the complication rate is higher [ 23 , 24 ]. Meanwhile, studies using allograft distal tibia, autogenous distal clavicle, and autologous scapular spine as grafts have also been reported [ [25] , [26] , [27] ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Wolff's law, 17 osteolysis and graft resorption might happen if the reconstructed glenoid is larger than its physiological size. 29 Therefore, the ability for glenoid restoration of the scapular spine is worth investigating. Rodriguez et al 36 found that the scapular spine was capable of achieving 28.2% glenoid restoration on average, compared with 31% in our results.…”
Section: Discussionmentioning
confidence: 99%